In vitro clonal propagation and evaluation of antibacterial activity of Benghal dayflower-Commelina benghalensis L. - Md. M. ISLAM; Md. A. AL MAMUN; Md. F. ALAM (Notulae Scientia Biologicae, 2020)
An efficient protocol for in vitro propagation of Commelina benghalensis was developed. Nodal segments were showed the superb explants in performance for shoot proliferation than other explants. On the other hand, BAP with auxin was better combination. The maximum (90.52) number of explants response and the highest (23.25) number of shoots per plant were obtained from nodal segments on MS medium fortified with 3.0 mg/l BAP+0.1 mg/l IBA. The highest shoot length (17.25 cm) was achieved on MS medium containing 3.0mg/l BAP+0.5mg/l IBA. In vitro proliferated shoots were transferred to full and half strength of MS media where 1.5 mg/l IBA on full strength of MS media was the best to fit for the maximum number (12.69) of roots formation per micro-shoot. Well rooted plantlets were transferred to soil and successfully acclimatized with 97% survival rate. Three extracts i.e. methanol, ethanol, Petroleum ether of C. benghalensis L and four concentrations of each extracts were used against five gram (+ve) and five gram (-ve) bacterial species for the screening of antibacterial activity. Ethanol extracts was the superior in performance. The susceptibility of tested pathogenic bacterial species was increasing compare with increasing of extracts concentration with few exceptions. The highest zone of inhibition was obtained against S. aureus (17.50 mm) and P. aeruginosa (17.44 mm) at 800 mg/l dose level of extracts. It was also noticed that Gram (+ve) bacterial species are more susceptible to Benghal dayflower crude extracts than Gram (-ve) bacterial species.